Association of total and bioactive serum sclerostin levels with bone metabolism in type 2 diabetes mellitus - Cyril Traechslin; Lilian Sewing; Sandra Baumann; Leticia Grize; Janina Vavanikunnel; Marius Kraenzlin; Christoph Henzen; Christian Meier (Journal of Clinical & Translational Endocrinology)
Background: Sclerostin has been associated with decreased bone turnover in patients with type 2 diabetes mellitus (T2DM). The relationship with bone turnover markers (BTMs) and bone mineral density (BMD) remains unclear. We investigate the relationship between total and bioactive sclerostin measured by three different assays with BTMs and BMD in patients with T2DM compared to healthy controls. Methods: Baseline data from the cross-sectional multicenter DiabOS-study in Switzerland were analysed. Total and bioactive serum sclerostin levels were measured using three different ELISA-based sclerostin assays (Sclerostin Biomedica, Sclerostin bioactive Biomedica and Sclerostin hsTECO). Sclerostin levels in patients with T2DM and controls were correlated with BTMs and BMD. Results: Data were analysed from 78 men and postmenopausal women with T2DM and 37 controls (aged 50–75 years). Serum sclerostin levels, adjusted for estimated glomerular filtration rate (eGFR), were higher in patients with T2DM compared to controls with all three assays. In a gender subgroup analysis, bioactive sclerostin levels remained significantly elevated in men with T2DM (T2DM, 106.8 ± 39.9 pmol/L; controls, 88.3 ± 21.3 pmol/L, p = 0.03).Univariate analysis showed consistent significant correlations with all sclerostin assays for age, eGFR, glycated hemoglobin A1c and diabetes duration. However, in multivariate analysis, eGFR remained the only significant determinant of serum sclerostin levels. Sclerostin levels in patients with T2DM showed significant positive correlations with BMD but no significant correlations with BTMs. Conclusions: We demonstrate a significant positive association of bioactive serum sclerostin with BMD at all measured sites in patients with T2DM, which may support its utility in the assessment of bone fragility in this population.